Tratamiento contable de la sección 17 y su incidencia en los impuestos diferidos, de la Empresa Textil Mil Colores, Cantón Santo Domingo, Período 2022 - Patricia Marisol, Miranda Escudero (2024)
ABSTRACT: The present research work aims to analyze the accounting treatment of section 17 and its impact on the deferred taxes of the Mil Colores Textile Company, Santo Domingo canton, period 2022. Therefore, the research used: a deductive, statistical and field method, with a non-experimental research design, whose approach was mixed. The population was the Thousand Colors Textile Company, however, for the analysis of the research work, the accounting department made up of 6 collaborators was taken into account. Information was collected through the entity's own documents, a five-question questionnaire with multiple response options on the Likert scale, and an interview. The results obtained through the analysis of documents were the product of the appraisal carried out in 2018; based on this information, a deferred tax asset of 8,277.03 USD was generated. While in 2022 with the sale of the Plotter for 18,500.00 USD, said tax could be reversed as determined by tax regulations, so within the analysis the impairment was 3,436.53 USD. That is, the reversal of the deferred tax was only 4,840.50 USD and not for the generation value of 8,277.03 USD, evidencing that the value generated by ID is not always the value that is reverted and that therefore the taxpayer can deduct in the income tax return. Finally, to verify the hypothesis, the chi square was applied with a significance level of 0.05, which yielded 8.67 > 7.81 where: the calculated chi square was greater than the tabulated one, therefore, the null hypothesis was rejected and accepted. the alternative: "The accounting treatment of section 17 affects the deferred taxes of the Mil Colores Textile Company, period 2022.".